Hydrologic response to climatic variations of a cascade of terraces - Co, Arlene Joy C.; Hernandez, Jaime Y. Jr.; Soriano, Mario A. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2013)
Climate change has extensive effect on the hydrologic cycle, and regionally, this is reflected to the changing availability of water. For agricultural systems highly dependent on water, such as terraces, these effects must be addressed by corresponding measures to maintain resilience and use of such hydraulic structures. In this study, the groundwater availability for the Ifugao rice terraces will be characterized to adjust agricultural practice, maintenance and operation in accordance to the changing climate. Unsteady state simulation will be done for the groundwater-soil intersection to determine the contribution of lateral flow to the terraces. Terrain characteristics will be determined by assuming several properties and determining which one is most suitable. The behavior of flow is examined with respect to the changes in slope, depth of the aquifer with respect to the water in the terraces. While there is no problem presented in the simulation in regard with the water in the terraces, simulation indicates low water table from the aquifer and dry forest.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Groundwater flow -- Philippines -- Ifugao; Terracing -- Philippines -- Ifugao